O desenvolvimento das funções psíquicas superiores de crianças de zero a três anos: a atenção e a memória - uma análise histórico-cultural - Faria, Waldirene dos Santos (2013)
This study addresses the development of Higher Psychological Functions of children aged zero to three years, specifically regarding attention and memory, and its relationship with education in daycare centers. The research question was: What concepts of the Historical- Cultural Theory underlie the need to potentialize the development of Higher Psychological Functions regarding attention and memory in children aged zero to three years in daycare centers? The objective of the study is: to identify Historical-Cultural Theory concepts that can support teaching activities for children aged zero to three years for developing higher psychological functions regarding attention and memory. The research was founded on dialectical and historical materialism and historical-cultural methods. The study methodology was based on bibliographic research, considered important to classify the study subject that was dispersed in several bibliographies. The methodological procedures were based on bibliographic reading recognition; key information localization; choosing bibliographies closer to the research object; and the final reading to achieve the proposed objectives. The result analysis shows concepts that can support teaching activities for developing Higher Psychological Functions in children aged zero to three years, such as cultural development, the main activity, mediation and the zone of proximal development. The results confirm that the development of infants is not universal and does not solely depend on the biological basis of human development. Social relationships are crucial to human development. School education is fundamentally responsible for the success of learning processes and child development nowadays, therefore, such learning must be intentional and planned, taking into account the specificities of child development, and also provide safe environmental conditions and varied cultural and intellectual experiences to promote mental development of children aged zero to three years in order to stimulate them. Higher Psychological Functions regarding Attention and Memory do not develop fully in the first year of life, however, intentional learning is required for significant psychological development. Introducing learning activities at an early age are the basis for subsequent complex psychological developments.